Effects of Adjuvant Administration of Macromolecules and Total Calories through Aggressive Parenteral Nutrition in Improvement of Neovascularisation of Infants with Retinopathy of Prematurity: A Literature Review - Tanto, Stefany; Octavius, Gilbert Sterling; Edgina, Alvita Suci (Talenta Publisher, 2022)
Introduction: Retinopathy of Prematurity (ROP) is almost exclusively in premature infants. With advanced care and technology, the prevalence of retinopathy of prematurity in babies is increasing, which means the incidence of preventable blindness in ROP is increasing. Objectives: Â To evaluate the effects of protein, glucose, lipids, and total calories from Aggressive Parenteral Nutrition (APN) in improving neovascularisation of ROP in premature infants. Methods: We searched PubMed, Ophthalmology Advance, Scientific Reports, and Science Direct using the terms